Operative treatment of isthmic spondylolisthesis in children: a long-term, retrospective comparative study with matched cohorts - Jalanko, Tuomas (Springer-Verlag, 2010)
The purpose of the present study was to compare the long-term clinical, functional and radiographic outcomes of young patients operated on before or at the onset of puberty (Children) and those operated on after that (Adolescents). The study group consisted of 298 patients operated on under the age of 20 years; 55 of them were operated on before or at the onset of growth spurt (29 females <12.5 years, 26 males <14.5 years). Preoperative data were retrieved from patients’ records. After mean follow-up of 17 years (10.7–26.3), physical examination, radiographic measurements and functional testing were performed by independent observers. SRS-24, Oswestry Disability Index (ODI), and Visual Analogue Scale (VAS) were utilised to evaluate health-related quality of life. The data were compared between the two age groups in the whole study population and in 41 pairs of patients matched by gender, operative method, severity of preoperative slip, and age at follow-up. Preoperatively, one-third of children did not have significant pain symptoms. They were operated upon for resistant postural anomalies in combination with high risk of slip progression. All of the adolescents had low-back pain as the main clinical symptom. The outcomes were satisfactory in both groups in the whole population (children vs. adolescents; low-grade slip: SRS-24: 95.9 vs. 92.0, ODI: 5.2 vs. 7.5, VAS low-back pain: 18.9 vs. 21.2; high-grade slip: SRS-24: 95.6 vs. 90.6, ODI: 3.4 vs. 6.9, VAS low-back pain: 10.5 vs. 22.1). The differences were statistically significant for ODI and VAS in high-grade patients in favor of the children. The clinical relevance of these differences seems to be minimal. The results of the comparison of the matched cohorts were comparably good. One-fifth of the whole study group had a non-union which did not affect the final outcome. In the children with high-grade slips, there was a mean slip improvement of 14 percentage points due to remodelling. The overall complication rate in the whole population was 7.7%. In conclusion, spinal fusion can be carried out at an early age for low- and high-grade spondylolisthesis with good long-term clinical, functional, radiographic and health-related quality-of-life outcomes when the indications are met.